Solvatochromism of π-extended Pyridinium-Thienylene-Phenolates - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Morales-Lovera, S (American Chemical Society, 2025)
The synthesis and solvatochromic behavior of two series of pyridinium-thienylene-phenolates, which differ in the relative orientation and length of their donor/acceptor pairs, are reported. Increasing the donor/acceptor distance significantly influences the spectral behavior of the dyes, transforming the negative solvatochromism exhibited by the shorter analogs into a highly symmetrical inverted solvatochromic response when the pi-system is increased. Through the application of multiparametric analysis, 1H NMR spectroscopy, and density functional theory (DFT) calculations, it was determined that the transition from negative to inverted solvatochromism is the result of an enhanced sensitivity of the pi-extended dyes to solvent polarizability, with the 2,4-thienylene ring present in the bridge playing a crucial role.